(untitled) (European Journal of Government and Economics, 2026)
This paper aims to contribute to a more comprehensive understanding of entrenched corruption in Bosnia and Herzegovina, through a comparative analysis with other Western Balkan countries. It is essential to determine whether corruption acts as a stimulus or deterrent to economic performance, considering empirical evidence suggesting that corruption may have a positive effect under certain conditions. The study utilizes indicators from the World Bank’s Worldwide Governance Indicators (WGI) database, along with gross domestic product per capita (GDP per capita) figures. The analysis employs both descriptive and regression methods applied to the aforementioned indicators over the period from 2010 to 2022. The effect of Corruption control on economic performance varies considerably across the observed countries. In Bosnia and Herzegovina, a significant negative relationship is observed. The results can help the authorities in the creation of policies and strategies that focus on the improvement of institutional quality and economic performance. This research fulfils an identified need to investigate the phenomenon of corruption in Bosnia and Herzegovina and neighbour countries in detail in recent time.